The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/antiox11112089
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Capability of Narcissoside in 6-OHDA-Exposed Parkinson’s Disease Models through Enhancing the MiR200a/Nrf-2/GSH Axis and Mediating MAPK/Akt Associated Signaling Pathway

Abstract: We assessed the antioxidant potential of narcissoside from Sambucus nigra flowers (elderflowers) in Parkinson’s disease models in vitro and in vivo. The results showed that narcissoside lessened the 6-hydroxydopamine (6-OHDA)-induced increase in reactive oxygen species (ROS) and apoptosis in SH-SY5Y cells. In the 6-OHDA-exposed Caenorhabditis elegans model, narcissoside reduced degeneration of dopaminergic neurons and ROS generation, and also improved dopamine-related food-sensitive behavior and shortened life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 102 publications
(111 reference statements)
0
15
0
Order By: Relevance
“…Simultaneously, the compound–target network analysis indicated that astragalin, 2″-(6-acetylglucosyl)­astragalin, sucrose, and narcissin were identified as the primary components responsible for the anti-inflammatory properties exhibited by SP extract. Previous studies have verified that both astragalin and low dose of sucrose could effectively alleviate the severity of colitis in mice , and also reported that astragalin and narcissin have potent anti-inflammatory effects against alveolar inflammation, osteoarthritis, and neuroinflammation by down-regulating MAPK and/or PI3K/Akt signaling pathways. Taken together, these findings collectively indicate that SP extract possesses the ability to alleviate DSS-induced colonic inflammation by suppressing macrophage activation through the inhibition of PI3K/Akt and MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 74%
“…Simultaneously, the compound–target network analysis indicated that astragalin, 2″-(6-acetylglucosyl)­astragalin, sucrose, and narcissin were identified as the primary components responsible for the anti-inflammatory properties exhibited by SP extract. Previous studies have verified that both astragalin and low dose of sucrose could effectively alleviate the severity of colitis in mice , and also reported that astragalin and narcissin have potent anti-inflammatory effects against alveolar inflammation, osteoarthritis, and neuroinflammation by down-regulating MAPK and/or PI3K/Akt signaling pathways. Taken together, these findings collectively indicate that SP extract possesses the ability to alleviate DSS-induced colonic inflammation by suppressing macrophage activation through the inhibition of PI3K/Akt and MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 74%
“…In the context of neurodegeneration in PD, aberrant MAPK signaling has been implicated as a key mediator of neuronal death in response to diverse insults such as 6‐OHDA. 36 In this study, we employed Western blotting to investigate the mechanism of action of CFE. Figure 4A–D shows that CFE dose‐dependently upregulated ERK but downregulated JNK and p38 signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The reserve of GSH is consumed by constant Fenton reaction induced by mass labile iron during stroke and neurodegenerative diseases, leading to a decline in the concentration of GSH as enzymatic reactants, which in turn inhibits GPX4 activity 247 . Moreover, evidence shows that promoting GPX4 activity and supplementation of GSH in neurodegenerative diseases and stroke both can mitigate oxidative stress and inflammatory pathology related to ferroptosis, thereby contributing to better preservation of executive functioning longitudinally 244,248–252 …”
Section: Ferroptosis: the Ending Of Iron Overloadmentioning
confidence: 99%
“…247 Moreover, evidence shows that promoting GPX4 activity and supplementation of GSH in neurodegenerative diseases and stroke both can mitigate oxidative stress and inflammatory pathology related to ferroptosis, thereby contributing to better preservation of executive functioning longitudinally. 244,[248][249][250][251][252] Therefore, GSH supplementation appears to be a promising target for stroke and neurodegenerative diseases. However, due to the isolation of BBB and the omnipresent γ-glutamyl transpeptidase, which is responsible for GSH cleavage, GSH supplementation in vitro fails to achieve the ideal effect in neurological protection.…”
Section: Reduction Of Gsh: the Collapse Of Antioxidant Systemmentioning
confidence: 99%